2021
DOI: 10.1111/obr.13198
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, calories, and obesity: A rapid systematic review and meta‐analysis of consumer knowledge, support, and behavioral effects of energy labeling on alcoholic drinks

Abstract: Summary Mandatory energy (calorie) labeling of alcoholic drinks is a public health measure that could be used to address both alcohol consumption and obesity. We systematically reviewed studies examining consumer knowledge of the energy content of alcoholic drinks, public support for energy labeling, and the effect of energy labeling of alcoholic drinks on consumption behavior. Eighteen studies were included. Among studies examining consumer knowledge of the energy content of alcoholic drinks (N = 8) and suppo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 47 publications
(53 reference statements)
2
49
0
Order By: Relevance
“…A recent study found that low-alcohol products are perceived to target non-traditional consumers (pregnant women) and occasions (weekday lunchtimes), suggesting potential challenges to their uptake [ 159 ]. In a recent systematic review and meta-analysis, Robinson et al [ 153 ] found moderate evidence that consumers are unaware of the energy content of alcoholic drinks, and that consumers support energy labelling. However, most studies found no effect of energy-labelling on actual or intended alcohol consumption; studies were generally of poor methodological quality and none were conducted in a real-life setting.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that low-alcohol products are perceived to target non-traditional consumers (pregnant women) and occasions (weekday lunchtimes), suggesting potential challenges to their uptake [ 159 ]. In a recent systematic review and meta-analysis, Robinson et al [ 153 ] found moderate evidence that consumers are unaware of the energy content of alcoholic drinks, and that consumers support energy labelling. However, most studies found no effect of energy-labelling on actual or intended alcohol consumption; studies were generally of poor methodological quality and none were conducted in a real-life setting.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent UK study produced similar results; most participants were inaccurate when estimating energy content of common alcoholic drinks with between 76-87% of participants making incorrect estimates, dependent on drink type [48]. In the same systematic review [47], studies examining consumer support for energy labelling of alcoholic drinks were examined [49,50].…”
Section: Consumer Need For Mandatory Energy Labelling Of Alcoholic Drinksmentioning
confidence: 97%
“…A number of studies have examined whether or not people are accurate when asked how many calories there are in common alcoholic drinks [45,46]. A recent systematic review and meta-analysis of eight studies that sampled participants from across Europe, North American and Australasia found that approximately 74% of sampled participants were unable to identify the number of calories in common alcoholic drinks accurately [47]. The review concluded there was only moderate (as opposed to strong) evidence that most people are unaware of the energy content of common alcoholic drinks, due to there being a relatively small number of included studies with some methodological limitations.…”
Section: Consumer Need For Mandatory Energy Labelling Of Alcoholic Drinksmentioning
confidence: 99%
See 2 more Smart Citations